La expresión musical y su incidencia en la inteligencia kinestésica corporal en niños y niñas del 2 inicial de la Unidad Educativa “Belisario Quevedo” de la provincia de Cotopaxi, cantón Pujilí, parroquia La Matriz en el año lectivo 2013-2014 - Chacha Estrella, Erika Alexandra (2015)
The present research work has important aspects about body kinesthetic intelligence. Since the beginning stimulation helps convey emotions, feelings, ideas, feelings, and to recognize different reactions in the body. Therefore it is very beneficial for parents to know that music is important since this in the womb of the mother. He drinks know differentiate between different sounds, like the voices of parents, in turn, influences the integral and emotional development. In the proposal it was decided to set the near reality because the guidelines proposed provide for the participation of children / as in workshops that allow them to use their bodily kinesthetic intelligence through a series of movements and exercises suggested. It also considers some materials that helps coordinate movement and balance your body. This research was conducted at the Education Unit Pujilí Belisario Quevedo Canton, Province of Cotopaxi, this process is totally perfected, with the purpose excellent acceptance of each of infants in developing the workshops. In the intellectual, emotional, cognitive, kinesthetic and social development of children favors the relationship with their environment into account individual differences.